Use of relative speed zones increases the high-speed running performed in team sport match play - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2015)
This study investigated the activity profiles of junior rugby league players competing in 3 distinct age groups (Under 13, 14, and 15), and 2 distinct playing standards (division 1 and 4). In addition, we reported global positioning system (GPS) data using predefined absolute speed thresholds and speed thresholds expressed relative to a players' individual peak velocity. Ninety male junior rugby league players, representing 1 of 6 teams competing in the Brisbane junior rugby league competition, underwent measurements of peak velocity (through a 40-m sprint) and GPS analysis during competitive matches. Data were described as both absolute speed zones and relative to the individual player's peak velocity. Absolute measures of moderate-, high-, and very high-speed running distances increased with age with the differences among groups typically small to moderate (effect size = 0.24-0.68) in magnitude. However, when data were expressed relative to a players' capacity, younger players and those from lower playing divisions exhibited higher playing intensities and performed greater amounts of high-intensity activity. Moderate and negative relationships (r = -0.43 to -0.46) were found between peak velocity and the amount of relative high-speed running performed. These findings suggest that individualization of velocity bands increases the high-speed running attributed to slower players and decreases the high-speed running attributed to faster players. From a practical perspective, consideration should be given to both the absolute and relative demands of competition to provide insight into training prescription and the recovery requirements of individual players.